Entrepreneurship in the Kebaya Fashion Industry: Its Impact on Monthly Business Turnove - Ni Ketut Laksmi Aryani (Atha Publishing Globalindo, 2026)
The fashion industry plays a significant role in supporting economic growth and creating business opportunities, particularly in the cultural fashion sector. One of Indonesia’s traditional fashion products that continues to attract consumer interest is the kebaya. The development of entrepreneurship in the kebaya fashion industry has contributed to business sustainability and increased market competitiveness. This study aims to analyze the impact of entrepreneurial activities in the kebaya fashion industry on monthly business turnover. The research employs a quantitative approach using survey methods to collect data from kebaya fashion entrepreneurs. Data were analyzed using descriptive statistics and regression analysis to determine the relationship between entrepreneurial practices and business performance. The findings indicate that entrepreneurial activities, including innovation, product diversification, digital marketing utilization, customer relationship management, and business networking, have a positive and significant effect on monthly business turnover. Entrepreneurs who actively adopt innovative strategies and digital platforms tend to achieve higher revenue growth compared to those relying on conventional business practices. The study highlights the importance of entrepreneurial capabilities in enhancing business performance and sustaining growth in the competitive fashion market.